Accessory gland size increases with sperm competition intensity in Cataglyphis desert ants - Degueldre, Félicien; Aron, Serge (Frontiers in Ecology and Evolution, 2024)
In many species, females have multiple mates, whose sperm compete for paternity. Males may subsequently invest in the increased production of sperm and/or seminal fluid. The latter is a complex mixture of proteins, peptides, and other compounds generated by the accessory glands (AGs) and is transferred to females along with a male's sperm. Seminal fluid is known to be a key determinant of competitive outcomes among sperm, and its production may trade off with that of sperm. We show that AG size-a proxy for seminal fluid production-has a positive and phylogenetically robust correlation with both sperm competition intensity and sperm production in nine species of Cataglyphis desert ants. These results indicate a lack of trade-off between sperm production and seminal fluid production. They underscore that sperm competition may strongly shape sperm traits and could drive reproductive performance in eusocial hymenopterans.